Theoretical calculation of influence of halogen at-oms (F, Cl, Br, I) on arylazopyridine (Azpy) ruthenium complexes behaving as photo sensitizers by DFT method - Kouakou Nobel, N'guessan; Wawohinlin Patrice, Ouattara; Kafoumba, Bamba; Nahossé, Ziao (International Journal of Advanced Chemistry, 2018)
Photosensivity prediction of several azopyridine ruthenium complexes by DFT and TDDFT methods was performed. g-RuX2 (Azpy) 2 and d-RuX2(Azpy)2 where X stands for F, Cl, Br and I were studied todetermine their activities when halide atoms shift. So, frontier orbital, NBO, NLMO and MLCT transitions as well as an excited lifetime of those complexes was determined. The main difference between them stems from both the electronegativity of the halide atoms and the structure of each complex. Hence, the rank of halide's electronegativity that is as followscp(F)>cp (Cl)>cp (Br)>cp (I) has been discovered to influence all the reactivity of the complexes regardless their structure. Herein, the comparison with the gap energy shows that the most reactive complexes are those with fluorine atom. Especially, d-RuF2(Azpy)2 was admitted to be the most active isomer. Moreover, NBO calculation discloses that the complex becomes less ionic when the electronegativity decreases from F to I atoms. Furthermore, the calculation of NLMO orbitals shows that the bonding Ru-X are very strong. However, this strength decreases also from F to I and the nature of the bonding move from ionic to metallic. Moreover, the bonding from Npy and N2 with Ru are known to be the same confirming the bidentate state of Azpy ligand. Regarding the electronic prediction, the eight complexes are surely assumed to display MLCT transitions that originate the photosensitivity. However, the complex that requires the least energy remains d-RuF2(Azpy)2. This result was also determined by analyzing the excited lifetime that is the ability for a complex to longer linger in the cationic state. At last, we found out that with iodine atoms, the azopyridine ruthenium complex cannot behave as photosensitize dye insofar as I atom hides the main orbitals from Ru regardless the symmetry.